The Effect of Mat Pilates exercise on Sleep Quality of Obese Young Adults - Maria Devina Putri Elvariani; Rahmi Isma Asmara Putri; Erna Setiawati; Hexanto Muhartomo (Faculty of Medicine, Universitas Diponegoro, Semarang, Indonesia, 2021)
Background: Obesity currently becomes one of the world's problems that can decrease a person’s quality of sleep. Pilates exercise was found to improve sleep quality in obese patients. Pilates exercise are safe to do because they don't involve jumping and running so they avoid trauma. Mat Pilates exercise is basic exercises that are done on the floor on a mat with simpler movements.Objective: To analyze sleep quality in obese young adults before doing Mat Pilates exercise and to compare changes in sleep quality for obese young adults before and after doing Mat Pilates exercise.Methods: This study used a quasi-experimental design applying one group pre-posttest. Samples were taken by purposive sampling with a total of 36 people who met the inclusion and exclusion criteria. The measurement of sleep quality used the Pittsburgh Sleep Quality Index (PSQI) questionnaire. Data analysis was tested for normality by using the Shapiro-Wilk test and the effect of Mat Pilates exercise on sleep quality in the treatment group using the Wilcoxon test. The difference is significant if p <0.05.Results: The average sleep quality for young adults before participating in the Mat Pilates exercise was 8.22 ± 1.87, while the average sleep quality for young adults after participating in the Mat Pilates exercise was 4.33 ± 0.77. The statistical test results showed that there was a significant difference (p = <0.001).Conclusion: There is an improvement in the mean value of sleep quality after doing Mat Pilates exercise.